Using system dynamics model and the statistical indicators for Road Map of "Green government departments" project In Iraq - ياسين الاء طلال; حمزة زينب فالح (Journal of Economics and Administrative Sciences, 2016)
Abstract The issue of the protection of the environment is a shared responsibility between several destinations and sectors, and constitutes a main subject in which they can achieve sustainable development. In the sectors of government programs can be set up towards the establishment of the government sector to the green environment, so to be the implementation of the road map for the "green government departments." Research question directed toward what environmentally friendly practices in the workplace and its importance and its impact on the preservation of the environment and raise employee morale and enhance productivity? And designate those factors is a necessity analysis of environmentally-friendly practices and still requires methodology and analysis. The objective of this research about the design and analysis of a dynamic model using the entrance to the analytical system for the government sector to the green environment, seeking to answer to the previous question, the researcher used the quasi-experimental approach the dynamic design in the analysis. Research focuses towards drawing the road map using dynamic analysis to the researcher proposed what it called "green government" and achieved through the application of green programs. The research to many of the results the most important of the analysis using the method of dynamic system illustrates the inter factors that contribute to the implementation of the roadmap for government departments green, such as using technology to reduce the consumption of paper and stationery, choose products information and communications technology, which holds, and done using appliances multifunctional, the use of products that allow dormancy function, automatic education programs for employees on environmental practices optimal, such as turn off appliances in the event of non-use, deletion League of unneeded files, the use of e-government services, check the carbon footprint of information technology equipment, recycling IT equipment the old way friendly, and also show this method is efficient in put interactive realized to the process of educating the employee for optimal environmental practices and strengthen behavioral change and build a culture of green environment, especially because they rely simulation in the analysis